Тhe principle of justice and legality in civil proceedings: interrelationships and contradictions - Maxatov, N.R.; Shan , Li (Bulletin of the Karaganda University “Law Series”, 2025)
This study examines the complex and multifaceted relationship between the concepts of the principles of jus tice and legality in the framework of civil procedure. Justice, as an ideal designed to ensure a balance of in terests of the parties and the protection of their rights, often comes into conflict with the formal requirements of legislation, which may give rise to norms that do not always take into account the individual circumstances of the case. The analysis focuses on how the guarantees of legality provided for by procedural law can both facilitate and hinder the achievement of fair solutions. Additionally, it examines how judicial practice and the doctrine of modern civil procedure interpret and implement these fundamental ideas, emphasizing the need for synergy between justice and legality to ensure effective and humane justice. Possible ways of harmoniz ing these two concepts are explored, which is important for the further development of civil procedure legis lation in accordance with international standards for the protection of human rights.